PERTIMBANGAN HAKIM TERHADAP GUGAT CERAI AKIBAT PERSELINGKUHAN DI PENGADILAN AGAMA TANJUNG KARANG(Studi Putusan Nomor 1321/Pdt.G/2024/Pa.Tjk) - Angela Merici L.P; Aprinisa; Baharuddin (JOURNAL OF LAW AND NATION, 2026)
This study aims to analyze the factors leading to divorce lawsuits due to infidelity and to examine the legal considerations of the judges in deciding such cases at the Religious Court of Tanjung Karang. The research focuses on Decision Number 1321/Pdt.G/2024/PA.Tnk, in which the plaintiff filed for divorce on the grounds that the respondent frequently met with her ex-husband without the knowledge or consent of her legal husband. The research problems addressed are: (1) What are the factors that cause a husband to file for divorce due to his wife’s infidelity in Decision Number 1321/Pdt.G/2024/PA.Tnk? and (2) How did the judge consider the legal aspects in deciding the divorce case based on infidelity?. This research employs a normative and empirical juridical approach, with data obtained through literature review and direct interviews. The findings indicate that the primary factor in the divorce was the loss of trust resulting from suspected infidelity, supported by evidence and witness testimony. In deciding the case, the judge considered the principles of justice, the protection of the rights of both husband and wife, as well as the provisions stipulated in Law Number 1 of 1974 in conjunction with LawNumber 16 of 2019 and the Compilation of Islamic Law. This research is expected to serve as a reference for legal practitioners and the public in understanding and resolving divorce cases due to infidelity in a fair and lawful manner.